Design of the human-machine interface for the cleaning-in-place system in the dairy industry - Belei, Oksana; Shtaier, Lidiia; Stasіuk Roman; Mirzojeva, Aleksandra (Eastern-European Journal of Enterprise Technologies, 2023)
The dairy industry must focus on sanitation and hygiene requirements to ensure product safety, control of detergents, tanks, pumps. Compliance with these requirements will provide conditions for the production of a high-quality dairy product, maintenance of technical and mechanical frequency at the enterprise, and prevention of the reproduction of harmful bacteria. Under these conditions, the problem of cleaning technical equipment from harmful residues on site is urgent. The object of the study is the basic processes in the Cleaning-In-Place system in the dairy industry. It is recommended to design a human-machine interface for on-site cleaning in the Siemens WinCC Flexible software. It is worth noting that the proposed interface takes into account the reduction of equipment downtime during the washing of technological equipment, a convenient user interface, and ease of maintenance. The state of use of existing visualizations of on-site cleaning interfaces that do not use simultaneous washing of two tanks with cleaning solutions (alkaline and acid) and the state of controlled values in selected washing lines were evaluated. Numerical evaluations of the results use modern programming technology and high information productivity of the user interface. A human-machine interface was designed with the possibility of parallel cleaning of two tanks at different ends of the workshop and the selection of recipes for different groups of tanks. This interface displays emergency messages, the status of the washing process of production lines and control based on data from sensors. The practical use of the obtained scientific results is that the designed interface can be used not only in the dairy industry but in any other food industry